Relationship of Picky Eater Behavior With Nutritional Status in Preschoolers - Wahyuni, Fitri; Reni, Ises; Yoza, Prima (Universitas Respati Yogyakarta, 2020)
The highest prevalence of malnutrition toddlers in Padang city in 2017 is known to reach 300 underfives found in Pauh sub-district. Malnutrition caused because eating one of which is the behavior of a picky eater. Picky eater occurs in pre-school age children experience changes in eating patterns generally picky eating. The purpose of this study was to determine the behavior of Picky Eater Relationship with Nutritional Status on Preschooler in kindergarten Al Hidayah Village Padang Pauh Subdistrict Cupak Tangah 2019. This type of research analytic survey with cross sectional study. The sampling technique is